Human interaction theory for sustainable city - Ibrahim, Filzani Illia; Nizarudin, Norhanis Diyana (IOP Publishing, 2019)
In relation to open spaces, Malaysia has received very little attention from researchers, unlike other countries where many studies have explored how human needs are fulfilled by urban open spaces. It is strongly believed that aspects such as the amount of urban open spaces per inhabitant, public parks and recreational areas are often mentioned as vital factors to make the city livable, pleasant and attractive for its citizens. This paper is undertaken to fill the knowledge gap of how human interacts in the urban open spaces that will then be developed as among the indicators for city sustainability. The objectives of this paper are to identify the human-nature and human-human interactions, at the same time identify the perceived benefits from physical, social and natural interactions towards open spaces. The expected outcome of this study is, it will help to emphasize the importance of citizen participation towards the open spaces and how it affects the level of sustainability. Furthermore, it will help in improving urban planning strategies and policy decision for the sustainability of the city.